EFFECT OF L-CYSTEINE ON POST THAW QUALITY OF NILI RAVI BUFFALO (BUBALUS BUBALIS) BULL SPERMATOZOA CRYOPRESERVED IN TRIS CITRIC ACID EXTENDER - F. Wadood; M. Aleem; A. Ijaz; N. Ahmad; M. S. Yousaf; D. H. Mughal; A. Javid 8and S. A. Mahmood (Journal of Animal and Plant Sciences, 2015)
This study was designed to determine effect of various concentrations of L- cysteine on frozen-thaw semen quality of Nili Ravi buffalo. Single ejaculate of four buffalo bulls (Nili-Ravi) was collected at weekly intervals for 5 weeks. Ejaculates of acceptable motility (≥70%) were pooled and semen was diluted by tris citric acid extender (TCAE; 300 mosm/kg osmotic pressure and ~7.0 pH) having 4 levels of L-cysteine (0.0, 2.0, 5.0 and 8.0 mM). Semen was equilibrated at 4˚C and packaged in 0.5 mL French straws with 20×106 spermatozoa/ straw and then frozen in liquid nitrogen. L-cysteine inclusion levels had non-significant (P> 0.05) effect on spermatozoa motility, viability, NAR, PMI and on lipid peroxidation. However, DNA damage in spermatozoa was significantly higher (P<0.05) in 8.0 mM L-cysteine. It was concluded that L-cysteine (2.0 and 5.0 mM) addition to cryopreserved semen had no significant effect on post thaw semen characteristics, except at 8 mM which adversely affected DNA integrity. This may be due to its toxicity at this concentration.
Keywords: cryopreservation; semen; spermatozoa; antioxidants; buffalo; L-cysteine